Serological and morpho-molecular characterization of papaya ringspot virus (PRSV) infecting the papaya (Carica papaya) in Tamil Nadu - MUTHULAKSHMI P; RAGAVENDRA MUDNUR; PARTHASARATHY SEETHAPATHY (The Indian Journal of Agricultural Sciences, 2024)
Papaya ringspot virus (PRSV) is wreaking havoc on papaya cultivation, leading to significant crop losses. Present study was carried out during 2022 and 2023 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu aimed to identify and characterize PRSV in four districts of Tamil Nadu. The incidence of the PRSV ranged from 32–100% in the surveyed districts. Samples displaying symptoms such as mosaic patterns, mottling, yellowing, puckering, shoestring appearance, oily stains on stems and petioles, deformed fruits, and concentric rings on fruits were collected for PRSV confirmation. The preliminary diagnosis of samples using DAS-ELISA showed the presence of PRSV in leaf and fruit skin samples but the absence of the virus in flower and seed samples. The existence of flexuous, filamentous rod- shaped particles measuring 809 nm × 15 nm in the tested leaf sample showed the incidence of Potyvirus, as revealed by transmission electron microscopy (TEM). Molecular characterization of PRSV in leaf and fruit skin samples was carried out using PCR with PRSV coat protein-specific primers, resulting in the amplification of an 850 bp product. Sequencing of the amplified products showed that the partial sequences of isolates CBE1-TN and ANR1-TN were 99.99% identical. Early detection of PRSV is imperative for implementing effective management strategies.